The political economy of state-business relations in Morocco - Boussaid, F (2016)
This thesis seeks to understand how state-business relations are affected by wider societal transformations. These transformations influence the potentially crony capitalist type of state society relations. I analyzed the evolution of state-business relations in Morocco. I highlighted three different factors which affected state-business relations and potentially can offset negative consequences of crony capitalism. Fragmentation of state institutions, political factions and economic actors and the maintenance of cross-cutting alliances by the monarchy have resulted in a fragmented-multiclass state. In addition, the changing nature of the role of the state in the economy had profound implications on state-business relations in Morocco. Paradoxically, the fragmented nature of Morocco, which is the result of cross-cutting coalitions between the monarchy and society, meant that the state did not fall exclusively in the hands of private interests. The pivotal position of the monarchy in economic and political life has enabled the monarchy to fragment opposition and forge diverse alliances to maintain its support-base. My theoretical approach using a macro-historical analysis coupled with process tracing of various policy domains proved to be a useful methodology for this type of research which falls in the nexus of politics and economics. Given this my thesis made a contribution to both Middle East studies as well as the wider literature on state-business relations. In addition, my research contributes to the wider debate on the resilience of monarchies in the aftermath of the Arab spring.